Effect of fibrous diets on feeding pattern, digestibility and physiological reactions in cattle and buffalo - BHATIA, S K; PRADHAN, K; SANGWAN, D C; SINGH, SADHANA; SAGAR, VIDYA (The Indian Journal of Animal Sciences, 2013)
The relative feed intake pattern, nutrient digestion and other related physiological parameters wen: studied in young male cattle (193 kg) and buffaloes (196 kg) by feeding wheat straw-groundnut-cake diet (9-10% CP) and sole berseem hay (11.5% CP), Buffaloes ate relatively less (p<0.05) dry maller per unit metabolic body size than caule. Irrespective of the lest diets, the average meal size on DM basis was consistently lower for buffaloes (69-71 g) than for cattle (72-83 g/hr/100 kg body Weight). Purther, buffaloes consumed lesser (34%) feed dry mailer (wheat straw-groundnut-cake) up to first 4 hr feeding than cattle (37.2%) indicating subsequent ingestion of larger poition of diet. However, with a change in dietary regime (berseem hay), a relatively higher proportion of offered feed dry matter (47% in buffaloes and 63% in cattle) was eaten by these ruminant species up to first 3 hr fceding. Such changes may be ascribed to differences in fibrous components of these two test diets. lbe digestion of feed nutrient exceeded (1<0.01) in buffaloes than in caule fed low-grade roughage. The related physiological parameters (blood urea and dietary regimes, though rectal temperature and pulse rate were lower (P<0.05) in buffaloes vis-a-vis cattle fcd berseem hay. The results inferred that eating pattern is governed by ruminant species and fibrous components of diet.